Current Sensor Based Electrical Leakage Detection System with Audible Alarm: Sistem Deteksi Kebocoran Listrik Berbasis Sensor Arus dengan Alarm Suara - Ainul Yaqin; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2026)
This study presents the development of an electrical cable leakage detection system based on a current sensor integrated with an audible alarm. General Background: Electrical leakage poses serious risks to safety, including equipment damage and fire hazards, requiring reliable detection systems. Specific Background: Conventional monitoring methods are often limited in responsiveness and require continuous manual observation. Knowledge Gap: There is a need for a real-time, automated, and low-cost system capable of detecting leakage current and providing immediate warning. Aims: This research aims to design and implement a leakage current detection system using the ACS712 current sensor and an Arduino microcontroller with a buzzer alarm feature. Results: The system detects leakage current exceeding a threshold of 450 mA, achieving accuracy above 90% and an average response time of 0.96 seconds, with stable real-time monitoring and clear LCD display output. Novelty: The integration of a current sensor with a direct audible alarm and simple microcontroller-based processing provides a practical and accessible detection mechanism. Implications: The proposed system offers a cost-effective solution for improving electrical safety in residential and small industrial environments through early warning capability. Keywords: Current Sensor, Leakage Detection, Arduino, Audible Alarm, Electrical Safety Key Findings Highlights Real-time monitoring identifies abnormal current conditions rapidly Sound alert activates immediately when threshold is exceeded System maintains stable operation under varied electrical loads